Development of HOTS-Based Interactive Worksheets Using Wizer.Me Media on Ecosystem (APPLICATION: Applied science in Learning Research, 2023)
ABSTRACTThe development of increasingly sophisticated technology has become an important means of achieving more effective and efficient educational goals. But behind that, there is a big demand for lecturers/teachers to develop skills in mastering technology and learning media. So it is necessary to develop learning media using the wizer.me application. The aims of this study are: 1) to describe the results of HOTS-based interactive worksheet validation using wizer.me media on ecosystem material according to media experts; 2) Describe the results of HOTS-based interactive worksheet validation using media wizer.me on ecosystem materials according to material experts. This research method is development using the ADDIE model. The instrument used was a validation questionnaire for media experts and material experts. Data analysis techniques in the form of validation and suggestions from the validator. The validation results from media experts showed that 82% were declared very feasible and the validation results from material experts showed 72.7% were declared feasible, indicating that wizer.me learning media on ecosystem material is suitable for use as a medium for learning ecosystem biology material.Keywords: Ecosystem, HOTS, Wier.Me, Worksheet.